ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA DISTRIBUTOR MULTILEVEL MARKETING NU SKIN DI SEMARANG - Suci Nuryani; Diana Aqmala (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2017)
Nu Skin Enterprises is a direct selling America and multilevelmarketingcompany that develops and sells personal care products and dietarysupplements (under the Pharmanex brand). Issuesthat form the basis of thisresearch is that Nu Skin has not been included in the 10best MLM dIndonesia by number of members and the members clarity andwebsite addressbased on MLMStars.net in 2012. The purpose of this study was to analyzetheeffect of the ability of the sales force, sales training and orientationaccuracy ofthe customer to the performance of agents multilevel marketingdistributors of NuSkin in Semarang . The population in this study is the distributor of Nu Skin multilevelmarketing agency in Semarang with a sample of 35 respondents wasobtained by purposive sampling technique, the distributor who has joined for3 months and have a monthly income and the amount of the bonus >Rp.1.000.000. Primary data was collected through questionnaires andanalyzed with multiple linear regression analysis . The results showed that the ability of the sales force and accuracy ofsalestraining has a positive effect on the performance of distributors agents.Whilecustomer orientation negatively affect the performance of distributorsagents.Variable accuracy of sales training (b2 = 0 , 534) became the largestfactoraffecting the performance of distributors agents. While the sales force'sabilityvariables (b3 = 0.419) became the lowest factor affecting theperformance ofdistributors agents .